Technique for Measuring Magnitudes and Phases of Voltage and Current in the Band-Selective Parallel LCR Circuit - Lamichhane, Hari Prasad (Journal of Institute of Science and Technology, 2019)
The current in the parallel LCR (inductor, capacitor and resistor) circuit depends not only on the magnitude of the applied electromotive force (emf) but also on its frequency. The circuit current in the parallel LCR circuit becomes very small in the resonating region, but at the same time, the potential difference across the LC tank becomes very large. These results are justified if there is a large induced current in the LC tank in such a way that the inductive and capacitive branch currents are nearly out of phase so that the vector sum of the currents be minimal. This theory can be verified by inserting a small series resistor in each branch. Finally, calculated magnitudes and phases of the potential differences across the newly connected resistors which are directly related to the magnitudes and phases of corresponding branch currents verify the theory.